2005
DOI: 10.1242/jeb.01939
|View full text |Cite
|
Sign up to set email alerts
|

Composite structure of the crystalline epicuticular wax layer of the slippery zone in the pitchers of the carnivorous plant Nepenthes alata and its effect on insect attachment

Abstract: SUMMARY The slippery zone situated below the peristome inside pitchers of most carnivorous plants from the genus Nepenthes is covered with a thick layer of epicuticular wax. This slippery zone is reported to play a crucial role in animal trapping and prey retention. In N. alata, the wax coverage consists of two clearly distinguished layers. These layers differ in their structure, chemical composition and mechanical properties, and they reduce the insect attachment in different ways. The lower la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 27 publications
12
164
4
1
Order By: Relevance
“…(c) Force measurements A 10 g load cell force transducer (World Precision Instruments, Sarasota, FL, USA) was clamped to a holder perpendicular to the horizontal plane of the substrate tested (for further details see Gorb et al [17]). Prior to the experiment, each substrate was briefly cleaned with ethanol and distilled water and dried in a nitrogen jet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Force measurements A 10 g load cell force transducer (World Precision Instruments, Sarasota, FL, USA) was clamped to a holder perpendicular to the horizontal plane of the substrate tested (for further details see Gorb et al [17]). Prior to the experiment, each substrate was briefly cleaned with ethanol and distilled water and dried in a nitrogen jet.…”
Section: Methodsmentioning
confidence: 99%
“…That is why adhesive setae, bearing fluid drops on their tips, can be easily contaminated by environmental particles. Plants possessing self-cleaning surfaces [12] are covered with wax crystals, which in many cases can break when insects walk on them and contaminate attachment devices [3,11,[13][14][15][16][17] (figure 1). It has been previously demonstrated that attachment forces are strongly reduced on contaminated feet [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…Structure-related properties of plant surfaces include the formation of low-adhesive surfaces, e.g. sliding of insects (Gorb et al 2005), and an increase in the reflection of visible light or absorption of harmful UV radiation (Barnes & Cardoso-Vilhena 1996;Pfündel et al 2006). Structures of plant surfaces are also relevant for surface wettability.…”
Section: Introductionmentioning
confidence: 99%
“…First, trapping is thought to be based on a slippery wax bloom on the inner pitcher wall of many Nepenthes species (Knoll 1914;Lloyd 1942;Juniper & Burras 1962;Juniper et al 1989;Moran et al 1999;Gaume et al 2002). It is made up of microscopic, epicuticular wax crystal platelets which give rise to antiadhesive surface roughness and easily break off, thus contaminating attachment structures and causing arthropods to slip (Knoll 1914;Juniper & Burras 1962;Gorb et al 2005). Second, it has been suggested that anaesthesia by narcotic alkaloids causes prey capture in Nepenthes madagascariensis (Ratsirarson & Silander 1996).…”
Section: Introductionmentioning
confidence: 99%